2010
DOI: 10.1002/chem.200902968
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Bond Responsible for the Fluorescence Modulation in an Amyloid Fibril Sensor

Abstract: An ultrafast intramolecular bond twisting process is known to be the responsible mechanism for the sensing activity of the extensively used amyloid fibril sensor thioflavin T (ThT). However, it is not yet known which one of the two possible single bonds in ThT is actually involved in the twisting process. To resolve this fundamental issue, two derivatives of ThT have been designed and synthesized and subsequently their photophysical properties have been studied in different solvents. It is understood from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 47 publications
(86 reference statements)
1
32
0
Order By: Relevance
“…However, upon binding to fibrils, the rotational freedom is apparently restricted and the excited state is readily populated. This concept was recently confirmed using a series of synthetic ThT analogs, which varied in their flexibility (22). The practical outcome of this mechanism is that ThT and its analogs can be used to spectroscopically quantify the amount of amyloid in a sample.…”
Section: Thioflavin Tmentioning
confidence: 87%
See 1 more Smart Citation
“…However, upon binding to fibrils, the rotational freedom is apparently restricted and the excited state is readily populated. This concept was recently confirmed using a series of synthetic ThT analogs, which varied in their flexibility (22). The practical outcome of this mechanism is that ThT and its analogs can be used to spectroscopically quantify the amount of amyloid in a sample.…”
Section: Thioflavin Tmentioning
confidence: 87%
“…Thioflavin T fluorescence is thought to increase when bound to Aβ fibrils because of the changes in the rotational freedom of the carbon–carbon bond between the benzothiazole and aniline rings (Figure 2A) (18,21,22). In the unbound state, the ultrafast twisting dynamics around this bond are thought to cause rapid self‐quenching of the excited state, resulting in low emission.…”
Section: Thioflavin Tmentioning
confidence: 99%
“…[26] The increased emission yield of ThT has been attributed to the restrictioni nt he nonradiative torsional motiona round its central CÀCs ingle bond in the amyloid fibrils. [29,30] ThT lacks protein-specificity as it binds to amyloid fibrils made up from all classeso fp roteins.N onetheless, it has been used for severald ecades for its high associationc onstant with the amyloid fibrils, and large sensitivityd ue to the enormous increasei ni ts emission intensity on association with amyloid fibrils. The actual mechanism for such as trong association of ThT with amyloid fibrils is still not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29] Comparative fluorescence studies with structurally tailored derivatives of ThT unequivocally established the fact that twisting of the central bond that connected the benzothiazole moiety and the dimethylaniline group was responsible for efficient nonradiative relaxation. [30] Recently, the simulation of photoelectron spectra of ThT by Ren et al revealed that torsional relaxation around the central bond took place in about 300 fs. [31] The sensitivity of the bond-twisting process on the microviscosity and rigidity of the surrounding medium was the main reason behind the excellent fluorescence sensing ability of ThT.…”
Section: Introductionmentioning
confidence: 99%